Monitoring Anticoagulation with Unfractionated Heparin on Renal Replacement Therapy. Which is the Best aPTT Sampling Site? - Anton, Florin Ioan (J Crit Care Med (Targu Mures), 2020)
BACKGROUND: Controlled anticoagulation is key to maintaining continuous blood filtration therapies. Objective: The study aimed to compare different blood sampling sites for activated partial thromboplastin time (aPTT) to evaluate anticoagulation with unfractionated heparin (UFH) in continuous renal replacement therapy (CRRT) and identify the most appropriate sampling site for safe patient anticoagulation and increased filter life span. METHOD: The study was a prospective observational single-centre investigation targeting intensive care unit (ICU) patients on CRRT using an anticoagulation protocol based on patient characteristics and a weight-based modified nomogram. Eighty-four patients were included in the study. Four sampling sites were assessed: heparin free central venous nondialysis catheter (CVC), an arterial line with heparinised flush (Artery), a circuit access line (Access), and a circuit return line (Postfilter). Blood was sampled from each of four different sites on every patient, four hours after the first heparin bolus. aPTT was determined using a rapid clot detector, point of care device. RESULTS: A high positive correlation was obtained for aPTT values between CVC and Access sampling sites (r (84) =0.72; p <0 .05) and a low positive correlation between CVC and Arterial sampling site (r (84) =0.46, p < 0.05). When correlated by artery age, the young Artery (1-3 day old) correlates with CVC, Access and Postfilter (r (45) = 0.74, p >0.05). The aPTT values were significantly higher at Postfilter and Arterial sampling site, older than three days, compared to the CVC sampling site (p<0.05). CONCLUSION: Considering patient bleeding risks and filter life span, the optimal sampling sites for safe assessment of unfractionated heparin anticoagulation on CRRT during CVVHDF were the central venous catheter using heparin free lavage saline solution, a heparinised flushed arterial catheter not older than three days, and a circuit access line.